The Role of Organizational Commitment in Improving Organizational Citizenship Behavior - Wilkanandya, Udhay Iqbal; Sudarma, Ketut (Management Analysis Journal, 2020)
This study aims to examine the effect of work life balance, personality and organizational commitment on organizational citizenship behavior. The sample used in this study was 165 respondents. The sampling technique uses incidental sampling. Data analysis methods use descriptive analysis, regression analysis, and path analysis using IBM SPSS. The results showed that work life balance was not significantly positive effect, while personality and organizational commitment had a positive and significant effect on organizational citizenship behavior and organizational commitment was able to mediate the relationship between work life balance and personality on organizational citizenship behavior. The suggestion from this research is that the company should be able to develop more policies that encourage employees to be eager to contribute. For further research that is examining the same aspects to use respondents who have a position in a relatively high job, such as supervisors and managers. To be compared between employees who have positions and not have positions.